Periphyton’s Chlorophyll-a Concentration in the Glass Substrate placed in the Salo River, Salo District, Kampar Regency - Rati Muspa; Asmika H Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is one of microorganisms that serve as primary producer in the aquatic environment. The periphyton contain Chlorophyll-a that is used for photosynthesis activity. To understand the concentration of Chlorophyll-a in glass substrate the Salo River, a study has been carried out in April-May 2015. The Chlorophyll-a data are used as a basis to calculate the primary productivity in the Salo River. There were 3 stations, in each station the water and periphyton were sampled once/week, for a 4 weeks period. The number of glass sampled in each station is following Berkman and Canova 2007, there are 30, 15 and 9 pieces in Stations 1, Stations 2 and Stations 3 respectively. The periphyton samples are brushed from the surface of glass substrate (10 cm x 3 cm). The chlorophyll-a concentration in the glass substrate ranged from 2.574 mg/m2 – 5.514 mg/m2. The chlorophyll-a concentration indicates that the trophic status of the Salo River is oligotrophic.Keywords : Salo River, Periphyton, glass substrate, chlorophyll-a